If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 19x + -8 + 2 = -2x + 2 + -8 Reorder the terms: -8 + 2 + 14x + 19x = -2x + 2 + -8 Combine like terms: -8 + 2 = -6 -6 + 14x + 19x = -2x + 2 + -8 Combine like terms: 14x + 19x = 33x -6 + 33x = -2x + 2 + -8 Reorder the terms: -6 + 33x = 2 + -8 + -2x Combine like terms: 2 + -8 = -6 -6 + 33x = -6 + -2x Add '6' to each side of the equation. -6 + 6 + 33x = -6 + 6 + -2x Combine like terms: -6 + 6 = 0 0 + 33x = -6 + 6 + -2x 33x = -6 + 6 + -2x Combine like terms: -6 + 6 = 0 33x = 0 + -2x 33x = -2x Solving 33x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 33x + 2x = -2x + 2x Combine like terms: 33x + 2x = 35x 35x = -2x + 2x Combine like terms: -2x + 2x = 0 35x = 0 Divide each side by '35'. x = 0 Simplifying x = 0
| 9y-6x=8 | | 7/9*9/14 | | 2(y-6)=y+3+2y | | -6(4x-6)+5(5x-6)-7=9-7 | | 8.2-3.5= | | (7b+3)(4b-3)=0 | | 6x-3x+x=-20 | | 3x-21+5x=-21 | | 3(4y-2)=-6+12y | | 3(q-15)=2q+10 | | 18m+24= | | -37-6x=14-3 | | x+0.03x=23.49 | | p(p-3)=0 | | 1/4(9x-20)= | | 5(a-2b)-3(a-2b)=0 | | 4=4x-4(3x+2) | | (8.2x-3.5)x=84.6 | | x+8=x+6 | | x+0.05x=23.29 | | 10r^2+8rs+15rs+12s^2= | | 8y+5=35 | | 15p-15=5p-5 | | 2x-z=v | | 6f-2/5 | | 3x-5(x+4)=2(p-x) | | 2/3(2x-1)10 | | 3x+2y+0.5z=20 | | -4=2x-18+5x | | 2cos3x/2 | | -(2x+1)=23 | | 3=6n |